THE EFFECT OF REPUTATION, STORAGE SECURITY AND TRUST ON CUSTOMERS' PREFERENCES IN CHOOSING SHARIA GOLD PAWNING - Ardiansyah, Kevin Septian; Susyanti, Jeni; Novianto, Abdullah Syakur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to determine the influence of Islamic bank reputation, gold storage security, and customer trust on customer preferences in choosing Islamic gold pawn products at BSI KCP Lawang. The background of this study is based on the increasing public interest in Islamic-based gold pawn services as a halal and safe short-term financial solution. The method used was a quantitative approach with a questionnaire distributed to 57 respondents who were gold pawn customers at BSI KCP Lawang. The data was analysed using multiple linear regression with the help of SPSS software . The results showed that the variables of reputation and storage security had a positive and significant effect on customer preferences, while the variable of trust had a positive but insignificant effect. These findings indicate that customers give more consideration to the image and security system of an institution when choosing sharia gold pawn services. This study is expected to contribute to the development of Islamic banking service strategies, particularly in increasing customer trust and loyalty.